KARAKTERISTIK KARYAWAN YANG BEKERJA PADA RUANGAN YANG MENGGUNAKAN AC DAN KELUHAN SICK BUILDING SYNDROME DI GEDUNG TVRI KOTA MEDAN TAHUN 2012 - Pramayana A.P Sinaga; Evi Naria; Surya Dharma (Lingkungan dan Kesehatan Kerja, 2012)
Characteristics of employees who work in room with air conditioner and has complaints of Sick Building Syndrome at office of TVRI Medan in 2012. Sick Building Syndrome is an accumulation of health problems related to air quality on an environment, or can also be defined as a non-specific health complaints from the occupants of the room air conditioned such as redness and watery eye, nasal congestion, sneezing, dry skin, and allergic to cold air. The purpose of the research is to identify the characteristics of employees working in air-conditioned based on: age, sex, length of employment, smoking habits, allergies, nutrition of state, and medical history to the incidence of Sick Building Syndrom. The type of study was descriptif of employees who are being in room with air conditioner including: age, sex, length of employment, smoking habits, allergies, nutrition of state, and medical history to the incidence of Sick Building Syndrome (SBS) at office of TVRI Medan. The result showed that is no characteristics of employees working a room with air conditioner including age, sex, length of employment, smoking habits, allergies, nutritional status, and medical history of complaints of sick Building Syndrome as lethargic complaints, headaches, dry throat, redness and watery eye, nasal congestion, and sneezing. The conclusions obtained from this research is none of employees who work in TVRI room with air conditioner has complaints of Sick Building Syndrome. Keywords: Sick Building Syndrome, Characteristics of Employees, Health Complaint